I Storbritanniens skygge? De socialdemokratiske forhandlingspositioner om Fælles Akten 1985-1986 - Pedersen, Rasmus Brun (Historisk Tidsskrift, 2015)
Bargaining in the Shadow of Britain? Explaining the Danish Social Democrats’ bargaining positions under the SEA IGC 1985-1986 The article conducts a detailed analysis of Danish positions in the dramatic negotiations of the SEA-Treaty in 1985-86. The initial, failed ratification in the Danish Parliament almost caused a major crisis in the relationship between Denmark and the EEC. This article examines the domestic play between the government and the opposition during the IGC in order to explain the initial Danish no. In some respects, the Social Democratic positions were remarkably stable and were designed to maintain the institutional status quo and thus internal party cohesion. However, the article also demonstrates that the Social Democrats’ hardline bargaining can be partially explained and justified by the party’s belief that the United Kingdom would reject the SEA-treaty. In other periods, short-term electoral concerns played a leading role, for instance in December 1985 and January 1986 when the Social Democratic party leadership attempted to avoid an internal confrontation over the common market question.